Radial Basis Function Assisted Interpolation For Electrical Machine Analysis - Halašta, Vítězslav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
The purpose of this paper is to introduce an interpolation adopting radial basis functions,that was used to analyze permanent magnet synchronous motor for aerospace application. Data usedfor this interpolation were obtained by performing an electromagnetic calculation using the finiteelement method.
Keywords: radial basis functions; interpolation; analysis; permanent magnet synchronous motor,aerospace; electromagnetic calculation; finite element method